Vaccination with a shared oncogenic tumor-self antigen elicits a population of CD8+ T cells with a regulatory phenotype. Issue 6 (30th November 2022) - Elizondo, C. Riccay; Bright, Jennifer D.; Bright, Robert K.
ABSTRACT: Cancer immunotherapy is a powerful tool for inducing antigen-specific antitumor cytotoxic T lymphocytes (CTLs). Next-generation strategies may include vaccination against overexpressed oncogenic tumor-self antigens. Previously, we reported vaccination against the oncogenic tumor-self antigen D52 (D52) was effective in preventing tumor growth. We recently reported that D52-vaccinated IL-10-deficient mice generated a significant memory response against tumor recurrence compared to wild-type mice and that vaccine-induced CD8+ IL-10+ T cells may possess regulatory function. Herein, we extended these studies by testing the hypothesis that D52-vaccine-elicited CD8+ IL-10+ T cells represent a distinct T cell population with a regulatory phenotype. C57Black/6J mice deficient in IL-10 or IFN-γ were vaccinated with the murine orthologue of D52; vaccination of wild-type (wt) mice served as a control for comparison. T cells were isolated from all three groups of vaccinated mice, and RNA was extracted from purified CD8+ T cells for deep sequencing and expression analysis. Chemokine receptor 8 (CCR8) and inducible co-stimulator (ICOS) were overexpressed in CD8+ T cells that produced IL-10 but not IFN-γ. These surface markers are associated with IL-10 producing CD4+ T regulatory cells thus supporting the possibility that CD8+ IL-10+ T cells elicited by D52 vaccination represent a unique regulatory T cell subset. The current phenotypic analyses of D52 vaccine elicited CD8+ T cells strengthen our premise that CD8+ IL-10+ T cells elicited by D52 tumor-self protein vaccination likely contribute to the suppression of memory CTL responses and inhibition of durable tumor immunity.